2013
DOI: 10.1002/jcop.21516
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy and Citizen Participation in Neighborhood Council in Iran

Abstract: This article examines the effects of self-efficacy on citizen participation (N = 250) in neighborhood councils in Tehran, Iran. Structural equation modeling was used to analyze the effects of self-efficacy on citizen participation. Results strongly supported the reliability and validity of the survey instrument. The findings revealed that 51% of the variance in citizen participation can be explained by self-efficacy. Citizens with higher self-efficacy are more likely to participate in neighborhood councils. C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…On the other hand, Peterson et al () have developed a scale that supports McMillan and Chavis’ () four‐dimensional PSC model, and Wombacher, Tagg, Bürgi, and MacBryde () and Barati et al () have provided strong support for the Peterson et al scale. Likewise, Lin and Israel's () exploratory approach actually revealed a model consistent with McMillan and Chavis’ original model.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, Peterson et al () have developed a scale that supports McMillan and Chavis’ () four‐dimensional PSC model, and Wombacher, Tagg, Bürgi, and MacBryde () and Barati et al () have provided strong support for the Peterson et al scale. Likewise, Lin and Israel's () exploratory approach actually revealed a model consistent with McMillan and Chavis’ original model.…”
Section: Resultsmentioning
confidence: 96%
“…A very important exception is Peterson et al's () 8‐item Brief Sense of Community Scale (BSCS), which was tested and confirmed in Wombacher et al (). Barati, Samah, & Ahmad () provided further evidence of the BSCS's validity by showing it is correlated with citizen participation. Similarly, Lin & Israel's () effort to test Proescholdbell et al's () 17‐item sense of community scale falls into the same category as Chipuer and Pretty (1999). Because Proescholdbell et al offered a specific model, Lin and Israel should have used a confirmatory rather than an exploratory approach, and so have not really attempted a replication of Proescholdbell et al's model.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Second, sense of community was assessed using three items asking students to indicate whether they had feelings of attachment to others in the school. Although existing theory (McMillan & Chavis, 1986) and previous research (Barati, Abu Samah, & Ahmad, 2012;Peterson, Speer, & McMillan, 2008;Wombacher, Tagg, Burgi, & MacBryde, 2010) on sense of community have described and validated four dimensions of the construct (i.e., needs fulfillment, membership, influence, and emotional connection), we focused on the emotional connection dimension for this study and included three items (Cronbach's a = .94; M -5.59; SD = 1.29), which were answered using a 7-point Likert-type scale that ranged from strongly disagree to strongly agree. Third, participation in extracurricular activities within the school asked students to indicate which orga nizations and activities they engaged in during the last year.…”
Section: Methodsmentioning
confidence: 98%
“…More recently, the BSCS factor structure has been tested cross‐culturally among the German Military (Wombacher, Tagg, Bürgi, & MacBryde, ); among adults from Malaga, Spain (Hombrados‐Mendieta, Gomez‐Jacinto, Dominguez‐Fuentes, & Garcia‐Leiva, ); and in a musical community in Puerto Rico (Rivera‐Segarra, Rivera‐Medina, & Varas‐Diaz, ). Also, studies have deductively tested SOC among college and university housing students (Townley, Kloos, Green, & Franco, ) and among an Iranian Community Council in Tehran (Barati, Samah, & Ahmad, ) to name a few. These investigations further confirmed the factor structure of the BSCS among the sampled groups of adults and, importantly, provided validity and reliability for its cross‐cultural use.…”
mentioning
confidence: 99%